DEVELOPMENT OF THE ECONOMY-MANAGEMENT COMPETENCIES BA IN ENGINEERING - Michail G. Minin; Vladislav G. Lizunkov (Высшее образование в России)
The paper deals with the development of bachelors’ of engineering economic and managerial skills in accordance with the requirements of employers under the Federal State Educational Standard of implementation. On the example of undergraduate training in«Engineering» at Yurga Technological Institute (branch) of the National Research Tomsk Polytechnic University, the list of economic and managerial skills bachelors of engineering has been updated with the new competencies based on questionnaires and analysis of employers’requests. The authors suggest an adjusted structural!functional model of economic and managerial skills of bachelors of engineering, view criteria and indicators to diagnose the readiness levels, present the approbation results of BA in mechanical engineering training model in the direction of «Engineering» at Yurga Technological Institute (branch) of Tomsk Polytechnic University in the period from 2011 to 2014.